Pengaruh Pola Asuh Diskriminatif Terhadap Kesehatan Mental - Handayani, Yeni Duwi; Musslifah, Anniez Rachmawati (Journal of Education and Learning Innovation, 2026)
Discriminatory parenting is the consistent unfair or differential treatment of children by parents, which then negatively impacts the child’s mental health. This study explores in depth the impact of discriminatory parenting and family violence on an individual’s mental health. This qualitative case study focuses on the experiences of a young adult who felt neglected and under-represented, especially financially, compared to her siblings. In addition, she experienced repeated physical violence from authority figures that left her deeply traumatized, compounded by the lack of protection from other family members. This condition triggered feelings of anger, injustice, disgust, and even suicidal ideation. Despite the various pressures, the participant showed significant resilience, developing adaptive coping mechanisms such as isolating herself, crying, and seeking comfort through art. Crucial support from close friends was a significant turning point that helped her through difficult times, demonstrating the vital role of social support in resilience. Spiritual beliefs also provided an internal source of strength that allowed her to find meaning in her suffering and view challenges as a process of self-strengthening. The results of this study confirm that discriminatory and abusive parenting can seriously damage mental health, but also highlight the extraordinary capacity of individuals to survive and find a way out. Practical implications emphasize the need for comprehensive psychological interventions, such as Client-Centered Therapy, CBT, Trauma-Informed Therapy, and Narrative Therapy, as well as the importance of psychoeducation and strengthening social support networks for vulnerable individuals.